1997
DOI: 10.1038/39062
|View full text |Cite|
|
Sign up to set email alerts
|

AMPA receptor-mediated regulation of a Gi-protein in cortical neurons

Abstract: Excitatory synaptic transmission in the central nervous system is mediated primarily by the release of glutamate from presynaptic terminals onto postsynaptic channels gated by N-methyl-D-aspartate (NMDA) and alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptors. The myriad intracellular responses arising from the activation of the NMDA and AMPA receptors have previously been attributed to the flow of Ca2+ and/or Na+ through these ion channels. Here we report that the binding of the agonist AMPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 21 publications
9
84
1
1
Order By: Relevance
“…Metabotropic properties of AMPA receptors were reported several years ago, when this receptor type was thought to be localized exclusively at postsynaptic density (Wang and Durkin, 1995;Wang et al, 1997;Hayashi et al, 1999;Perkinton et al, 1999). We have now identified AMPA receptors of developing and mature axon terminals as key molecules of a pathway, activated by neuronal activity, which leads to presynaptic MAPK activation.…”
Section: Ampa Induces Presynaptic Mapk Activation Independently From mentioning
confidence: 96%
See 1 more Smart Citation
“…Metabotropic properties of AMPA receptors were reported several years ago, when this receptor type was thought to be localized exclusively at postsynaptic density (Wang and Durkin, 1995;Wang et al, 1997;Hayashi et al, 1999;Perkinton et al, 1999). We have now identified AMPA receptors of developing and mature axon terminals as key molecules of a pathway, activated by neuronal activity, which leads to presynaptic MAPK activation.…”
Section: Ampa Induces Presynaptic Mapk Activation Independently From mentioning
confidence: 96%
“…The molecular mechanisms at the basis of these effects are mostly unknown, and ion influxes through the receptor may only partially account for the observed changes (Lee et al, 2002). Interestingly, several studies have shown that postsynaptic AMPA receptors, in addition to their function as ion channels, also possess metabotropic properties, leading to the activation of mitogen-activated kinase (MAPK) or to the inhibition of adenylate cyclase (Wang and Durkin, 1995;Wang et al, 1997;Hayashi et al, 1999;Perkinton et al, 1999). It is presently not known whether presynaptic AMPA receptors also have metabotropic properties.…”
Section: Introductionmentioning
confidence: 99%
“…It also has a role in synaptic targeting and/or trafficking of AMPA receptors through interactions with some of the receptor-associated proteins such as SAP97 (Leonard et al, 1998), which may function to modulate synaptic AMPA receptor dynamics and thus mechanisms of synaptic plasticity. The GluR1 subunit has also been shown to interact with an inhibitory G protein in cortical neurons (Wang et al, 1997), thus indicating a metabotropic function of the AMPA receptor. Reduction in levels of the GluR1 subunit, as noted in cortical regions in the present study, might therefore result in either excitatory or inhibitory effects on AMPA receptormediated neurotransmission.…”
Section: Discussion Behavioral Measure Of Dependencementioning
confidence: 99%
“…One possibility is that these cells have an unusual type of picrotoxin-sensitive GABA receptor that has slow metabotropic effects. Although metabotropic actions have been described at some "ionotropic" receptors (Wang et al, 1997;Kawai and Sterling, 1999), no such actions have been reported at picrotoxin-sensitive GABA receptors. A more likely possibility is that the modulation is mediated by another, unknown substance and that GABA may act to suppress the synthesis or release of this substance.…”
Section: Where Does the Modulation Of Glycinergic Inhibition By Gaba mentioning
confidence: 99%